Antimicrobial Peptides in Gut Health: A Review - Gong, Tao; Fu, Jie; Shi, Lexuan; Chen, Xin; Zong, Xin (Frontiers in Nutrition, 2021)
Animal antimicrobial peptides (AMPs), known as broad-spectrum and high-efficiency antibacterial activity, are important effector molecules in innate immune system. AMPs not only have antimicrobial, antiviral and antitumor effects but also exhibit important effects in vivo, such as anti-inflammatory response, recruiting immune cells, promoting epithelial damage repair, and promoting phagocytosis of bacteria. However, research on the application of AMPs is incomplete and controversial. This mini-review mainly introduces the classification of AMPs, biological functions, as well as the mechanisms of action, expression rules, and nutrition regulation from three perspectives, aiming to provide important information for the application of AMPs.